2020
DOI: 10.1002/elan.202060265
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O/CuO Electrocatalyst for Electrochemical Reduction of Carbon Dioxide to Methanol

Abstract: Herein, we report the controlled and direct fabrication of Cu2O/CuO thin film on the conductive nickel foam using electrodeposition route for the electrochemical reduction of carbon dioxide (CO2) to methanol. The electrocatalytic reduction was performed in CO2 saturated aqueous solution consisting of KHCO3, pyridine and HCl at room temperature. CO2 reduction was carried out at a constant potential of −1.3 V for 120 min to study the electrochemical performance of the prepared electrocatalysts. Cu2O/CuO shows be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Cu + or Cu 0 species exists in Sn 1 /V o ‐CuO‐ x , but it is hard to distinguish from XPS spectra due to the similarity in the binding energies. Therefore, the Cu Auger L 3 M 45 M 45 transition was also performed to provide more insight into the electronic structures and surface state (Figure S8), [14] indicating the coexistence of Cu + and Cu 0 species on Sn 1 /V o ‐CuO‐ x .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cu + or Cu 0 species exists in Sn 1 /V o ‐CuO‐ x , but it is hard to distinguish from XPS spectra due to the similarity in the binding energies. Therefore, the Cu Auger L 3 M 45 M 45 transition was also performed to provide more insight into the electronic structures and surface state (Figure S8), [14] indicating the coexistence of Cu + and Cu 0 species on Sn 1 /V o ‐CuO‐ x .…”
Section: Resultsmentioning
confidence: 99%
“…Theq uasi-operando X-ray photoelectron spectroscopy (XPS) revealed the composition and valence state of the catalysts.T he binding energies of 495.4 and 486.9 eV for Sn 3d 3/2 and Sn 3d 5/2 indicated the oxidation state of Sn [41] (Figure S5,6). Figure S7 showed that the Cu 2p XPS spectra of Sn 1 /V o -CuO-x exhibited significantly distinct Cu features compared with that of Sn 1 /CuO.I tc an be seen that the Cu 2+ peaks disappeared gradually as the increasing H-plasma treatment time.C u + or Cu 0 species exists in Sn 1 /V o -CuO-x, but it is hard to distinguish from XPS spectra due to the similarity in the binding energies.T herefore,t he Cu Auger L 3 M 45 M 45 transition was also performed to provide more insight into the electronic structures and surface state (Figure S8), [14] indicating the coexistence of Cu + and Cu 0 species on Sn 1 /V o -CuO-x.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past 100 years, CO 2 concentration has greatly risen by 100 ppm. Given its cost-efficiency, non-toxicity, and abundance, CO 2 has attracted a lot of attention for transforming it into useful chemicals such as methanol, formic acid, and hydrocarbons [1][2][3][4][5]. From among the materials to which CO 2 can be transformed, methanol is of paramount importance for its potential uses in fuel cells and internal combustion engines [6].…”
Section: Introductionmentioning
confidence: 99%